Women Rights, Wage Labour and Sexual Exploitation: A Labour Law Analysis of 'Sex Work'. Issue 2 (December 2017) - Roy, Shanie
This article first deconstructs the argument of the 'pro-sex-work' lobby that the prostitution of women should be defended as workers' rights. It then proposes that the feminist abolitionist movement should fully integrate the issue of labour rights for women at the centre of its political discourse.